Detection of biologically active substances in Aristolochia clematitis L. herb by HPLC and determination of antimicrobial activity of this raw material - Burda, Nadiia; Pohodina, Lala; Kyslychenko, Victoria; Martynov, Artur (Annals of Mechnikov's Institute, 2021)
Introduction. Aristolochia clematitis L. is a perennial herbaceous plant, family Aristolochiaceae. At present, there are some difficulties with the use of Aristolochia clematitis in medicine. They are primarily due to side effects, including nephropathy. Therefore, today scientists from different countries are conducting in-depth research to study the chemical composition and pharmacological activity to understand the safe use of drugs based on raw materials of plants of the genus Aristolochia L. There are positive results in determining the antimicrobial and cytotoxic activity of plants of the genus Aristolochia. In general, analyzing the scientific literature, we can conclude that information on the chemical composition and scientifically proven pharmacological action of Aristolochia clematitis is not enough. The aim of the study was to identify biologically active substances in Aristolochia clematitis herb, collected within the budding and blooming phase, by HPLC. Also conducting a screening study of the antimicrobial activity of these raw materials. Materials and methods. Aristolochia clematitis herb was collected within the budding and blooming phase in Kharkiv and Khmelnytskyi Regions, Ukraine, in May-June 2019/2020. The chromatographic study of tested herb specimens was performed at a Shimadzu HPLC-system, ser.20 liquid chromatograph equipped with a diode matrix detector under the following conditions: Phenomenex Luna C18 column, dimensions: 250 mm х 4,6 mm, particle size 5 μm; column temperature 350С; detector wavelength 330 nm; mobile phase flow rate 1 ml/min; introduced sample volume 5 μl. The components were identified by their retention time and conformity of their UV spectra to standard substance. To determine the antimicrobial activity of Aristolochia clematitis herb, we conducted a screening study of extracts from this raw material. Extracts were obtained in the ratio of raw materials: extractant 1:10. Purified water and 50%, 70% and 96% ethanol were used as extractants. Determination of the sensitivity of strains of microorganisms was determined by a known method by the method of wells using Mueller-Hinton medium. Evaluation of antibacterial activity was performed on the diameter of the growth retardation zones: 10 mm – the microorganism is not sensitive to the test extract, 10-15 mm – the microorganism is insensitive to the test extract; 15-25 mm – microorganism sensitive to the studied extract, 25 mm and above – microorganism highly sensitive to the studied extract. The following strains of microorganisms were used in the study: Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Proteus vulgaris ATCC 4636, Pseudomonas aeruginosa ATCC 27853, Bacillus subtilis ATCC 6633, Candida albicans ATCC 653. Research results. Experimental study using these chromatographic conditions revealed compounds of phenolic nature, namely ferulic acid, kaempferol and rutin, in the studied objects. In addition, the presence of aristolochic acids AA-I and AA-II was simultaneously detected. It should be noted that the qualitative composition of the detected compounds of Aristolochia clematitis herb, collected within the budding phase, did not differ from the herb collected within the blooming phase. The antimicrobial activity of Aristolochia clematitis herb, collected within budding phase, and herb collected within the blooming phase, did not differ significantly. However, it should be noted that it was still slightly higher in the herb collected within the blooming phase. It should be noted that the most pronounced antimicrobial activity was in the extracts obtained with 70% ethanol, the lowest – purified water. Microorganisms such as Staphylococcus aureus, Pseudomonas aeruginosa and Bacillus subtilis were highly sensitive to the action of extracts Aristolochia clematitis. Conclusions. Thus, the results obtained on the study of the chemical composition of Aristolochia clematitis herb show the prospects of its further in-depth study of the compounds of phenolic nature, as well as the determination of their quantitative content. In addition, the screening determination of antimicrobial activity of the studied types of raw materials revealed the optimal extractant, namely 70% ethanol and raw materials – Aristolochia clematitis herb, within the blooming phase, which should be used for further study. The high antimicrobial activity of Aristolochia clematitis herb suggests the possibility of using extracts from it in medicines for external use. Keywords: Aristolochia clematitis L., chemical compounds, HPLC, antimicrobial activity. DOI: 10.5281/zenodo.5499700